Research on Deflection of Partial Steel Fiber Reinforced Concrete Beams with BFRP Bars - Hui Dong; Shengping Chen; Hangyu Li; Jianbo Zhang (Advances in Materials Science and Engineering, 2022)
In this study, the flexural behavior tests of steel fiber reinforced concrete beams with BFRP bars under static load are carried out by means of statics experiment and theoretical analysis. A total of seven beams were designed for this experiment, and the effects of two factors on the mid-span deflection of the beams were investigated with the steel fiber incorporation rate (0%, 0.5%, 1%, 1%/0.5%, 1.5%) and the height of steel fibers in the concrete layer in the compression zone (180 mm, 210 mm, 300 mm) as the main variables. In this study, based on the existing research results and combined with the actual test results, the formulae for calculating the cracking section moment of inertia applicable to BFRP reinforced steel fiber (full section/pressure zone reinforced) concrete beams are derived. At the same time, the results obtained from the formula and the results of the ACI code in the United States are compared with the data of the results obtained from this test, and the calculated results of this formula are in good agreement with the actual values.